Elbow Arthroscopy for Treatment of Osteochondritis Dissecans of the Capitellum - Melissa L. Carpenter BS; Jose F. Vega MD; Jintong Liu BS; Michael J. Murray BS; Trevor A. Poulson MS; Zeeshan A. Khan BA; Juan Bernardo Villarreal-Espinosa MD; Nikhil N. Verma MD (Video Journal of Sports Medicine)
Background: Osteochondritis dissecans (OCD) of the elbow is an idiopathic lesion of subchondral bone resulting in delamination and sequestration with or without articular cartilage involvement; for patients with persistent symptoms, surgical treatment is often recommended. While traditionally performed in the supine or prone position, arthroscopic debridement and microfracture of OCD of the capitellum in the lateral decubitus position permits strategic arm positioning and placement of portals to optimize visualization and reduce the risk of damage to neurovascular structures. Indications: Arthroscopic debridement and microfracture in the context of OCD is utilized when conservative management with rest, physical therapy, and nonsteroidal anti-inflammatory drugs does not provide improvement in pain. This technique is also preferred for smaller defects not suitable for fragment fixation or osteochondral autograft transplantation. Technique Description: After induction of anesthesia, the patient is placed in the lateral decubitus position with the operative extremity supported with an arm holder at 90°. The left side is then prepped and draped sterilely. A diagnostic arthroscopy of the elbow is first performed to identify any concomitant pathologies. The OCD defect is then mobilized with a probe to enhance visualization. The lesion is thoroughly debrided with a shaver to create a stable rim and the base decorticated with a curette. An arthroscopic microfracture instrument is used to create microfracture sites at the base of the lesion. Results: It is the senior author’s belief that management of OCD with arthroscopic debridement and microfracture in the lateral decubitus approach provides superior visualization and allows free manipulation of the joint throughout the procedure. This facilitates direct treatment of the OCD lesion to ensure a stable rim is created while permitting comprehensive evaluation of the joint. Additionally, the risk of iatrogenic injury to nearby neurovascular structures while instrumenting the joint is diminished with proximally placed portals. Discussion/Conclusion: Arthroscopic debridement and microfracture for OCD in the lateral decubitus position with the operative extremity supported proximally in an arm holder has been shown to optimize arthroscopic viewing of the OCD lesion, thereby ensuring the lesion is stabilized and comprehensively treated. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.